HISTOCHEMICAL ANALYSIS OF GASTROINTESTINAL MUCOSUBSTANCES OF FRESH WATER FISH MASTACEMBELUS ARMATUS INDUCED BY HELMINTH PARASITE PROCAMALLANUS SP. FROM LATUR DISTRICT (MS) INDIA (International Journal of Food and Nutritional Sciences, 2022)
The present study deals infection of particular parasite and particular impact on host fish species.Different histochemical reactions showed localization of different chemicals. With the Moreover, thehistochemical investigations provide an insight into the nature of various physiological and pathologicalprocesses in the gastrointestinal tract occurred due to parasites. It has been observed that the differentconstituents are stimulated by particular parasite and particular loss in different organs of the digestive systemof the fish studied.Histochemical study may provide a valuable with low cost-effective tool for the diagnosis of diseasesin histopathology, parasitic investigation and for the researchers in histopathology. The present study includesthe histochemical analysis of Procamallanus species infected fish intestines in Mastacembellus armatus.